The relative age effect in a professional football club setting - Mujika, I.; Vaeyens, R.; Matthys, S. P. J.; Santisteban, J.; Goiriena, J.; Philippaerts, R. (Journal of Sports Sciences, 2009)
The relative age effect is an uneven distribution of birth date favouring subjects born in the initial months of a selection year. This study compared the birth-date distributions between several subgroups of Basque football players to identify whether the relative age effect is influenced by age and/or skill level. The study comprised 13,519 players including 114 senior professionals from the Spanish league's AC Bilbao over 21 seasons; over the season 2005-2006, it comprised elite youth (n = 189) from the same club's academy; regional youth (n = 4382) U11-U14 locally federated players; school youth (n = 8834) U10-U11 locally registered school district players. Differences between the observed and expected birth-date distributions were tested based on data from the general Basque male population. Significant chi-square values were followed up by calculating odds ratios and 95% confidence intervals (CI) for the quartile and half-year distributions to examine subgroup differences in the relative age effect. Birth-date distributions of all groups of players showed a significant bias towards early birth in the selection year compared with the reference population (senior, ?23 = 24.4, P < 0.001; elite youth, ?23 = 59.1, P < 0.001; regional youth, ?23 = 41.4, P < 0.001; school youth, ?23 = 40.9, P < 0.001). Between-group comparison revealed that the relative age effect incidence progressively increased with a higher level of involvement in youth football. This bias represents a significant loss of potential youth football talent.